Factors Influencing Image and Loyalty of Halal Tourism Destinations in Yogyakarta, Indonesia - Soewito , Deffrin Glennino; Andriansyah, Yuli; Putra, Bintang Paula (Universitas Islam Indonesia, 2023)
Indonesia's rich cultural and geographical diversity positions it as a global tourist destination, with Yogyakarta standing out for its cultural heritage. This study investigates the factors influencing the image and loyalty of halal tourism destinations in Yogyakarta, addressing the growing demand for halal-compliant tourism in a predominantly Muslim country. The research aims to analyze the impact of various factors, including halal food, social environments, facilities, services, staff behavior, attire, perceived value, satisfaction, and trust, on shaping the image and loyalty of halal tourism destinations. A quantitative approach was employed, utilizing surveys to collect data from 160 respondents visiting selected hotels and attractions in Yogyakarta. Data analysis included multiple regression testing and classic assumption tests to ensure robustness and reliability. The findings reveal that all examined variables significantly influence the image and loyalty of halal tourism destinations. Key contributors include halal food, social environments, and staff behavior. Tourists rated satisfaction, perceived value, and trust highly, though areas like halal-specific information and services require enhancement. The model demonstrates strong predictive power, with 90% of loyalty and image variations explained by the analyzed factors. This study emphasizes the importance of addressing faith-based needs to sustain and enhance Yogyakarta’s halal tourism appeal. Recommendations include developing halal-compliant infrastructure, improving information services, and implementing targeted marketing strategies to attract and retain Muslim tourists. These insights provide actionable strategies for stakeholders in the tourism sector, contributing to the broader literature on halal tourism.